Implementasi Pemasaran Digital Dalam Meningkatkan Penjualan Risoles Mayones Dinta - Adinda, Utami Putri Wahyu; Suprayitno, Suprayitno; Yoppi, Syahrial (Edumedia Solution, 2023)
In Indonesia Risoles Mayonnaise is served as a snack, but in its native country, France, Risoles are consumed as the main food. Risoles Mayonnaise, a processed product from â€Risol Mayo Dintaâ€ is a home industry product that was founded in 2020. In this digital period, conventional marketing is considered to be not optimal and not developing in the business world. An effort to get and keep consumers is the main thing to be realized in the business world which is increasingly competitive. Therefore, in solving this problem, a digital-based marketing strategy is carried out which can optimize sales of Risol Mayo Dinta. Digital marketing is in the form of a marketplace application with methods that can be applied consisting of three levels, namely analysis, creating an online marketplace, and implementation. Digital marketing suggested as a solution can make it easier for Risol Mayo Dinta to implement its digital marketing strategy. Also, if Risol Mayo Dinta continues to implement digital marketing that is built consistently and stably, of course it can optimize digital-based technology, sales will soar, and affect the profits to be obtained.